SPATIO-TEMPORAL DYNAMICS OF MANGROVE COVER 1985-2025 BASED ON GEOSPATIAL ANALYSIS IN REMBANG - Suryaningtias, Sabna; Jafron Wasiq Hidayat; Muhammad Helmi (RADJA PUBLIKA, 2026)
Mangroves are coastal vegetation that lives in tidal zones, providing ecosystem services such as biota habitats, abrasion barriers, breakbreaks, and significant carbon sequestration for climate change mitigation. However, the mangrove ecosystem in Indonesia, including in Rembang District, which includes Pasarbanggi, Tireman, and Kabongan Lor Villages, has been degraded due to land conversion into ponds, logging, and reclamation. This study aims to analyze the spatio-temporal dynamics of mangrove cover in 1985-2025 in Rembang District using MVI based on Landsat 5 (1985, 1995), Landsat 7 (2005), and Sentinel-2A (2016, 2025) satellite imagery. The analysis was carried out with a composite of NIR, Green, and SWIR Bands, digitization, cropping, cover classification, and analysis of mangrove cover changes. The results of the study show that the area of mangrove cover has experienced very significant fluctuations. The period 1985–2005 was dominated by heavy degradation (-67.93%), while the period 2005–2025 recorded a very strong recovery of mangrove ecosystems (+339.56%), with the high cover class increasing from 17.39 ha to 27.40 ha. The success of rehabilitation and reduced land conversion have succeeded in restoring the area of mangrove forests while improving the quality of mangroves in Rembang District. Keywords: Spatio-temporal dynamics, Rembang, Mangrove, MVI, Remote Sensing